(untitled) (Analysis in Theory and Applications, 2011)
Let A, B be two unital C^*−algebras. By using fixed point methods, we prove that every almost unital almost linear mapping h : A → B which satisfies h(2^nuy)= h(2^nu)h(y) for all u U(A), all y A, and all n=0,1,2, …, is a homomorphism. Also, we establish the generalized Hyers–Ulam–Rassias stability of *−homomorphisms on unital C^*−algebras.